Nail apparatus melanoma initially diagnosed as nail matrix blue nevus: a case report with dermatoscopy and dermatopathology - Bengu Nisa Akay; Aylin Okcu Heper; Luc Thomas; Brigitte Balme; Simon Clark; Cliff Rosendahl (Mattioli1885, 2017)
We present a case of nail apparatus melanoma in a 50-year-old woman presenting as new and changing longitudinal melanonychia of the right thumb. Very heavy melanin pigmentation involving both the epidermis and dermis interfered with dermatopathological assessment, which initially leads to a diagnosis of nail matrix blue nevus. After consultation with a specialist multidisciplinary clinic the diagnosis was revised to invasive melanoma, a diagnosis consistent with the clinical and dermatoscopic assessment.